Changes in BNP, hs-CRP and TIMI risk index with addition of tirofiban during primary percutaneous coronary intervention for acute STEMI: a prospective observational cohort study - Kurt, Ibrahim Halil; Demirkol, Sait; Unal, Ilker; Batur, Mustafa Kemal (TURKISH SOC CARDIOLOGY, 2012)
Objective: This study aimed to investigate the relationship of tirofiban, added to the treatment of acute ST-elevation myocardial infarction (STEMI) patients underwent primary percutaneous coronary intervention (PCI), with changes in the TIMI risk index (TRI) of TIMI flow, B-type natriuretic peptide (BNP) and high-sensitive C-reactive protein (hs-CRP) levels. Methods: This single-center, prospective observational cohort study included 102 consecutive patients who were admitted with the diagnosis of acute STEMI (70 male

54.9 +/- 10.4 years). Primary PCI was applied to all cases with STEMI, who applied to our hospital in the first 6 hours due to chest pain complaints. Tirofiban was administered to one group (n=55) (male: 36

54.1 +/- 11.3 years), while the other group was not given tirofiban (n=47) (male: 34

55.9 +/- 9.1 years). The primary end-point was TIMI flow 2 or 3 for reperfusion after primary PCI. Chi-square test, paired t-test or Wilcoxon signed rank test, Spearman correlation analysis and Kaplan-Meier survival analysis were used for statistical analysis where appropriate. Results: BNP level remained the same in the tirofiban group, whereas a significant increase was observed in the group that was not treated with tirofiban (105.9 +/- 126.8 versus 261.3 +/- 202.3 pg/ml p<0.001). The hs-CRP level tended to rise significantly in both groups despite the treatment (tirofiban group - from 0.67 +/- 0.66 to 0.90 +/- 0.44 mg/L, p=0.015, non tirofiban group - from 0.51 +/- 0.43 to 1.08 +/- 0.74 mg/L, p<0.001). BNP and hs-CRP values remained the same in cases with TIMI 2 flow in the tirofiban group, whereas a significant increase was detected in the post-treatment BNP (before 97.8 +/- 122.3 after 281.6 +/- 217.3 pg/ml, p=0.011) and hs-CRP (before 0.65 +/- 0.69

after 1.33 +/- 0.80 mg/L, p=0.028) values in the group not treated with tirofiloan. In patients with TIMI 3 flow, BNP (tirofiban group before 146.5 +/- 114.2

after 184.4 +/- 139.4 pg/ml, p=0.011, non tirofiban group before 172.1 +/- 297.9

after 295.9 +/- 384.9 pg/ml, p<0.001) and hs-CRP levels (tirofiban group before 0.66 +/- 0.58

after 0.92 +/- 0.65 mg/L, p=0.011, non tirofiban group before 0.81 +/- 0.74

after 1.45 +/- 1.23 mg/L, p<0.001) were found to be similarly reduced in both treatment groups p<0.05. Three patients with minor hemorrhage did not need blood transfusion. Conclusion: It was concluded at the end of them PCI application in STEMI that the addition of tirofiban treatment in patients with >= TIMI 2 flow and anterior location MI could decrease the expected rise in BNP and CRP values. (Anadolu Kardiyol Derg 2012

12: 107-14)
Keywords: Acute myocardial infarction; tirofiban; percutaneous coronary intervention; TIMI risk index; B-type natriuretic peptide; high-sensitive C-reactive protein